Kritik Sosial Pers Terhadap Pemerintah Terkait Polusi Udara di DKI Jakarta - Rizky Anendya Wicaksana; Eka Nada Shofa Alkhajar (Universitas Sebelas Maret (UNS), 2024)
Editorial is a section in a newspaper that contains opinions and social criticism from the newspaper print media on current issues or events. Using Abar's (1997) perspective, this study analyzes the social criticism contained in the editorials of Media Indonesia, Kompas, Jawa Pos, and The Jakarta Post. The main focus is social criticism towards the government regarding air pollution in DKI Jakarta. The research method used is qualitative content analysis. The data collection techniques used in this research are observation and documentation conducted at the Surakarta Press Monument. All selected editorials were obtained from the institution. For sampling, this research used purposive sampling technique. Meanwhile, this study used source triangulation technique for data validity. This study found: (1) The four newspaper editorials convey social criticism of the government regarding the phenomenon of air pollution in DKI Jakarta, which has become a troubling and even harmful problem; (2) The four newspapers have different ways of delivery. Media Indonesia, The Jakarta Post and Jawa Pos tend to be more straightforward in delivering their social criticism. Meanwhile, Kompas tends to be less straightforward in conveying it.